Layered ternary sulfide CuSbS2 nanoplates for flexible solid-state supercapacitors1. Issue 25 (7th July 2015) - Ramasamy, Karthik; Gupta, Ram K.; Sims, Hunter; Palchoudhury, Soubantika; Ivanov, Sergei; Gupta, Arunava
<x xml:space="preserve">Abstract</x> Supercapacitor devices using nanoplates of ternary layered sulfide CuSbS2 exhibit very good performance with excellent cyclic stability, flexibility and can be operated over a wide temperature range.